LOCAL CULTURE AND MORALITY ATTACHMENT TO TPACK FRAMEWORK OF PRE-SERVICE ENGLISH TEACHERS WITHIN THE CHALENGE OF THE 21st CENTURY SKILLS - Akmal, Akmal (International Journal of Education, 2017)
In 2045, Indonesia is determined to have a golden generation in order to improve the nation's competitiveness. However, in reality the condition of teenagers today is very alarming. The data show about 93 out of 100 elementary school students have already consumed pornography; about 21 out of 100 young women have abortions; some 135 teenagers become victims of violence every day; 5 out of 100 adolescents contract sexually transmitted diseases; 63 out of 100 teens have sex before marriage. School teachers should take active roles in minimizing such unhappy figure and prepare the golden generation. This article proposes local culture and local moral to complete the Technological Pedagogical Content Knowledge (TPCK+) within the challenge of the 21st century skills. The objectives are to provide pre-service English Teachers at Universitas PGRI Semarang and pre-service English teachers in general with the ability to develop English course content in the studentsâ€™ cultural context as well as local characters and to equip the pre-service teachers with the 21st century skills. The subjects were 345 pre-service English Teachers who took the TEFL, Teaching Media, and ESP Courses during the academic year of 2015/2016 and 2016/2017. The data were collected through observation, teaching practice, and self-evaluation. The results show 84.92% of the students were included under the category of â€œgoodâ€ and â€œvery goodâ€ in pedagogical skills, 77.38 % in pedagogical content knowledge, and 87.53 % in cultural and local wisdom context in content development, but only 51.58% in technological knowledge. For improving technological knowledge of the pre-service students, there should be more training on the use of technology before and during the process of teaching and learning of pre-service English teachers.